The impact of using CLT approach in developing learning English language skills of Saudi EFL students: students’ perceptions - Hakami, Adeeb (European Scientific Journal, ESJ, 2025)
This study investigates Saudi EFL students’ attitudes towards the Communicative Language Teaching (CLT) approach to the four basic skills, namely listening, speaking, reading, and writing. Interviews were conducted as data collection followed by thematic analysis using a qualitative research design. Results show that CLT promotes engagement and fluency, specifically in speaking and listening, but there are also obstacles to CLT such as teachers’ readiness, resource inequality, and linguistic anxiety. The study confirms the need for curriculum innovations, teacher training, and digital learning incorporation to support the establishment of CLT. Suggestions for follow-up research are investigating the long-term application of CLT and the use of blended learning solutions within Saudi EFL learning environments.